2020
DOI: 10.1029/2019rs006979
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Turbulence Parameters Using ARIES ST Radar and GPS Radiosonde Measurements: First Results From the Central Himalayan Region

Abstract: Turbulence in the atmosphere plays a vital role in controlling the surface, lower and upper tropospheric dynamics. Here, we have utilized a newly installed Aryabhatta Research Institute of Observational Sciences (ARIES) Stratosphere Troposphere (ST) radar at the high‐altitude subtropical site in the central Himalayan region (Nainital, 29.4°N, 79.5°E, 1793 m above mean sea level) for the first ever estimation of turbulence parameters from this unique location. We have used radar observations made in years 2017 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Previous studies have shown that the turbulence parameters calculated using MST radar data are in good agreement with the calculated results using radiosonde data [11][12][13]. Kantha and Hocking [13] and Li et al [14] compared the ε calculated by radar data and radiosonde data. They used the radar datasets of Harrow VHF (very high frequency) radar (42.04 • N, 82.89 • W) and MAARSY (Middle Atmosphere Alomar Radar System) radar (69.03 • N, 16.04 • E), respectively.…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…Previous studies have shown that the turbulence parameters calculated using MST radar data are in good agreement with the calculated results using radiosonde data [11][12][13]. Kantha and Hocking [13] and Li et al [14] compared the ε calculated by radar data and radiosonde data. They used the radar datasets of Harrow VHF (very high frequency) radar (42.04 • N, 82.89 • W) and MAARSY (Middle Atmosphere Alomar Radar System) radar (69.03 • N, 16.04 • E), respectively.…”
Section: Introductionmentioning
confidence: 55%
“…This paper gives the statistical results of turbulence parameters, but how the turbulence parameters change during synoptic processes needs to be further investigated. For example, the correlation analysis in this paper shows that the turbulence parameters above 15 km may be mainly affected by the turbulence intensity; the results of Khoma et al [15] show that the seasonal characteristics of turbulence parameters are related to gravity waves in the Antarctic stratosphere; and Li et al [14] calculated ε under different Ri, and the results showed that the median values of ε when Ri < 1 is 3.2 times that of when Ri > 1. From October to the following May, in the height layer of 1 km above and below the tropopause, there is no apparent seasonal difference in the monthly average profile of ε. Additionally, log(ε) increases sharply with a rate of 0.25 m 2 s −3 km −1 , derived by linear regression.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…The same power spectra analysis of the vertical velocity can be used to identify a cut off point of Brunt-Vaisala frequency, while vertical temperature profile (Fig. 10e) can used to derive a complete profile of the Brunt-Vaisala frequency along the altitude [20,21].…”
Section: Vertical Atmospheric Profiling Measurementsmentioning
confidence: 99%
“…VHF Stratosphere-Troposphere radars and UHF wind profilers are commonly used to estimate turbulence kinetic energy (TKE) dissipation rate ε from Doppler spectral width (hereafter, noted 2σ 𝑜𝑏𝑠 ) in the atmosphere (e.g., Hocking, 1983Hocking, , 1985Hocking, , 1986Hocking, , 1999Fukao et al, 1994;Cohn, 1995, Kurosaki et al, 1996Bertin et al, 1997, Delage et al, 1997Naström and Eaton, 35 1997, Dole et al, 2001, Jacoby-Kaoly et al, 2002, Satheesan and Murthy, 2002Naström and Eaton, 2005;Wilson et al, 2005, Kalapureddy et al, 2007Singh et al, 2008;Dehghan and Hocking, 2011;Kantha and Hocking, 2011;Dehghan et al, 2014;Wilson et al, 2014;Hocking et al, 2016;Li et al, 2016;Kohma et al, 2019;Jaiswal et al, 2020;Chen et al, 2022). Several models have been proposed to relate 2σ 𝑜𝑏𝑠 to ε.…”
Section: Introductionmentioning
confidence: 99%